Effects of monocyte chemoattractant protein‐1, macrophage inflammatory protein‐1α, and interferon‐α2a on P450 enzymes in human hepatocytes in vitro - Maciej Czerwiński; Krystal Gilligan; Kevin Westland; Brian W. Ogilvie (Wiley, 2019)
Abstract Some immunomodulatory agents stimulate the release of cytokines capable of suppressing P450 enzymes and potentially affecting pharmacokinetics of coadministered medications. Cytokines released in response to an immunomodulator in the blood ex vivo can be used to screen for the potential for drug‐drug interactions. Tilsotolimod, an investigational agonist of Toll‐like receptor 9, stimulated the release of macrophage chemoattractant protein‐1 (MCP‐1), macrophage inflammatory protein‐1α (MIP‐1α), and interferon‐α2a (INF‐α2a) in blood obtained from healthy donors. Although tilsotolimod did not directly affect CYP1A2, CYP2B6, or CYP3A4 expression or activity, the cytokines stimulated by the drug reduced CYP1A2 and CYP2B6 enzyme activities in cultured human hepatocytes. This study sought to identify which cytokines were responsible for tilsotolimod's indirect effects on P450 enzymes in vitro. A 72‐h treatment with recombinant human chemokines MCP‐1 and MIP‐1α did not alter CYP1A2, CYP2B6, CYP2C8, CYP2C9, CYP3A4, or signal transducer and activator of transcription 1 (STAT1) mRNA expression or CYP1A2, CYP2B6, or CYP3A4/5 enzyme activity in cocultures of human hepatocytes and Kupffer cells. INF‐α2a, at 2.5 ng/mL but not at the lower concentrations applied to the cells, increased CYP1A2 and STAT1 mRNA by 2.4‐ and 5.2‐fold, respectively, and reduced CYP2B6 enzyme activity to 46% of control. This study established that INF‐α2a, but not MCP‐1 or MIP‐1α, mediated tilsotolimod effects on CYP1A2 and CYP2B6 expression in human hepatocytes.